2007
DOI: 10.1007/s00268-007-9270-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Surgical Management of Total Colonic Aganglionosis

Abstract: TCA is difficult to diagnose; but once it is diagnosed correctly and treated by corrective surgery, outcomes seem promising. Martin's operation brought about a good outcome and enabled patients to have acceptable bowel habits. The prognosis is highly dependent on the extent of aganglionosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Normal or near-normal growth and development certainly contributed to the good QOL of the majority of our patients. It should be noted that in some other series, growth was as satisfactory as in ours [3,6], whereas in others it was compromised, particularly after many years [31]. Anemia and iron and vitamin B12 deficiencies have been described in TCA patients in whom the terminal ileum had to be resected [13], but although this was not especifically investigated in our patients, they showed no clinical symptoms.…”
contrasting
confidence: 50%
See 1 more Smart Citation
“…Normal or near-normal growth and development certainly contributed to the good QOL of the majority of our patients. It should be noted that in some other series, growth was as satisfactory as in ours [3,6], whereas in others it was compromised, particularly after many years [31]. Anemia and iron and vitamin B12 deficiencies have been described in TCA patients in whom the terminal ileum had to be resected [13], but although this was not especifically investigated in our patients, they showed no clinical symptoms.…”
contrasting
confidence: 50%
“…Of course, one-third of the patients experience occasional episodes of soiling, particularly when the stools are liquid, but, as shown by our scores, most can be considered continent and are satisfied in this respect. This experience is not very different from that reported for other large series of TCA [3,6,10,13,21,30,32]. However, at least one thorough study comparing the long-term results of 15 cases of TCA and 15 of rectosigmoid HD from the surgical and psychological standpoints at 7 to 17 years after operation found that in a substantial proportion of patients in both groups continence was defective and consequently, patients experienced psychological difficulties [19].…”
mentioning
confidence: 46%
“…In fact, all available surgical techniques were designed to preserve the anal canal, and therefore, sensation and the sphincter mechanism. Soiling can occur even when a technically adequate pull-through and colo-anal anastomosis is performed and can also occur in patients who do not have factors known be associated with higher rates of fecal incontinence, such as Down's syndrome [12,13] and total colonic aganglionosis [14][15][16]. This is evidence of our incomplete understanding of the pathogenesis, treatment, and management of HD.…”
mentioning
confidence: 92%
“…Comparing these findings to prior literature is difficult, given that clinical definitions for constipation, postoperative obstruction symptoms, and incontinence vary greatly across studies and may be captured differently based on the data collection method used. 65 In fact, certain studies report no HD patients experiencing constipation 69 70 vs 30%–76% after surgery. 48 66 Similarly, cohort studies document ranges of incontinence from 19% to 82%.…”
Section: Discussionmentioning
confidence: 99%